Book Review - Halvorssen, Anita (Columbia Journal of Environmental Law, 2020)
OUR COMMON FUTURE: THE WORLD COMMISSION ON ENVIRONMENT AND DEVELOPMENT, Geneva, Switzerland, Oxford University Press, 1987. Pp. 400.